The rise and fall of consumption in the '00s - Yuliya Demyanyk; Dmytro Hryshko; Maria José Luengo-Prado; Bent E. Sørensen (Federal Reserve Bank of Boston, 2015)
U.S. consumption has gone through steep ups and downs since 2000, but the causes of these fluctuations are still imperfectly identified. We quantify the relative statistical impact of income, unemployment, house prices, credit scores, debt, expectations, foreclosures, inequality, and refinancings on consumption growth for four subperiods: the "dot-com recession" (2001-2003), the "subprime boom" (2004-2006), the Great Recession (2007-2009), and the "tepid recovery" (2010-2012). We document that the explanatory power of different factors varies by subperiods, implying that a successful modeling of this entire decade needs to allow for multiple determinants of consumption. Unemployment, income, and debt are important determinants of consumption during all four periods.
Keywords: E21; E37; 330